A role for lymphocytes and cytokines on the eosinophil migration induced by LPS - Hugo C Castro-Faria-Neto; Carmen M Penido; Andréa P Larangeira; Adriana R Silva; Patrícia T Bozza (Memorias do Instituto Oswaldo Cruz, 1997)
In the present work we review the existing evidence for a LPS-induced cytokine-mediated eosinophil accumulation in a model of acute inflammation. Intrathoracic administration of LPS into rodents (mice, rats or guinea pigs) induces a significant increase in the number of eosinophils recovered from the pleural fluid 24 hr later. This phenomenon is preceded by a neutrophil influx and accompanied by lymphocyte and monocyte accumulation. The eosinophil accumulation induced by LPS is not affected by inhibitors of cyclo or lipoxygenase nor by PAF antagonists but can be blocked by dexamethasone or the protein synthesis inhibitor cycloheximide. Transfer of cell-free pleural wash from LPS injected rats (LPS-PW) to naive recipient animals induces a selective eosinophil accumulation within 24 hr. The eosinophilotactic activity present on the LPS-PW has a molecular weight ranging between 10 and 50 kDa and its effect is abolished by trypsin digestion of the pleural wash indicating the proteic nature of this activity. The production of the eosinophilotactic activity depends on the interaction between macrophages and T-lymphocytes and its effect can not be blocked by anti-IL-5 monoclonal antibodies. Accumulated evidence suggest that the eosinophil accumulation induced by LPS is a consequence of a eosinophilotactic cytokine produced through macrophage and T-cell interactions in the site of a LPS-induced inflammatory reaction.